Myeloma bone disease imaging on a 1st-generation clinical photon-counting detector CT vs. 2nd-generation dual-source dual-energy CT: computed tomography - Winkelmann, Moritz; Hagen, Florian; Le-Yannou, Lucie; Weiss, Jakob; Riffel, Philipp; Gutjahr, Ralf; Faby, Sebastian; Nikolaou, Konstantin; Horger, Marius (European radiology, 2023)
Subjective and objective image quality comparison of bone microstructure and disease-related abnormalities in multiple myeloma patients using a 1st-generation dual-source photon-counting detector CT(DS-PCD-CT) and a 2nd-generation dual-source dual-energy (energy-integrating detector) CT (DS-EID-CT).
Online veröffentlicht: 9. November 2022
Gesehen am 06.08.2024